Assessment of Porous Carbons Derived from Sustainable Palm Solid Waste for Carbon Dioxide Capture - Siti Noraishah, Ismail; Usman D., Hamzah; Noor S., Nasri; Murtala M., Ahmed; Rahman, Mohsin (Elsevier, 2014)
Potentials of solid agro-wastes from palm processing mills (palm kernel) for producing low cost porous carbons were investigated. The study deals with the use of palm kernel shell based porous carbons as adsorbents for CO2 capture. Carbonization of the palm kernel shell (PKS) was carried out at 700 °C followed by CO2 activation. The porous carbons were characterized using Fourier transform infrared spectroscopy (FTIR), thermogravimetric and derivative thermogravimetric (TG/DTA) analysis, scanning electron microscopy (SEM), proximate analysis, ultimate analysis and nitrogen adsorption tests. The adsorption equilibrium of CO2 on palm kernel shell activated carbon was measured using a static volumetric technique. Adsorption of CO2 on the porous carbons was conducted at 30 °C for pressures up to 4 bars. The equilibrium data were simulated using the Freundlich and Langmuir isotherms, with both models having R2 > 0.98. The experimental kinetic data was fitted to the pseudo-first-order, pseudo-second-order and Elovich equations, while the adsorption mechanism was evaluated using the Webber-Moris intra-particle diffusion model. Higher CO2 uptake of 7.32 mmol/g was obtained for PAC (palm kernel activated carbon) at 30 °C and 4 bars. PAC adsorbed 23.52 kg CO2/t PKS. The findings revealed the potential of palm shell as a viable and sustainable biomass for preparation of activated carbon for gas adsorption applications.